2020
DOI: 10.1002/cphc.202000630
|View full text |Cite
|
Sign up to set email alerts
|

Binding Mode Multiplicity and Multiscale Chirality in the Supramolecular Assembly of DNA and a π‐Conjugated Polymer

Abstract: Water-soluble π-conjugated polymers are increasingly considered for DNA biosensing. However, the conformational rearrangement, supramolecular organization and dynamics upon interaction with DNA have been overlooked, which prevents the rational design of such detection tools. To elucidate the binding of a cationic polythiophene (CPT) to DNA with atomistic resolution, we performed molecular simulations of their supramolecular assembly. Comparison of replicated simulations show a multiplicity of CPT binding geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…It also was shown that rigid−flexible complexes release many more polyions by increasing salt concentration due to limited conformational flexibility. More specific simulations for polythiophene and DNA complexation were presented by Surin and co-workers as shown in Figure 2B and C. 29,69 Figure 2B shows single-stranded (ss) polyA-PT and polyT-PT complexation. Analysis revealed that electrostatic interactions played a pivotal role in PT-DNA complexation.…”
Section: Analytesmentioning
confidence: 99%
“…It also was shown that rigid−flexible complexes release many more polyions by increasing salt concentration due to limited conformational flexibility. More specific simulations for polythiophene and DNA complexation were presented by Surin and co-workers as shown in Figure 2B and C. 29,69 Figure 2B shows single-stranded (ss) polyA-PT and polyT-PT complexation. Analysis revealed that electrostatic interactions played a pivotal role in PT-DNA complexation.…”
Section: Analytesmentioning
confidence: 99%
“…Following this paper, the method was extended to measure chirality and shape . In the following years, the method was applied to study the role of approximate symmetry in numerous molecular systems, including symmetry of crystals, , distortion paths of inorganic complexes, reactive processes, host–guest interactions, molecular dynamics and symmetry of biomolecules. , Application of this approach beyond chemistry were also documented, e.g., in archeology. , …”
Section: Introductionmentioning
confidence: 99%